Co‐existence of BRAF V600E‐mutated malignant melanoma and BRAF V600E‐mutated Langerhans cell histiocytosis: A case report. (28th November 2021) - Goto, Keisuke; Yoshikawa, Shusuke; Kiyohara, Yoshio; Kukita, Yoji; Miura, Keiko; Oishi, Takuma
Abstract: Langerhans cell histiocytosis (LCH) is a neoplastic condition of Langerhans cells, and can be associated with other neoplasms, especially BRAF ‐mutant hematological tumors and papillary thyroid carcinoma. Here we present the first case of co‐existing LCH and low cumulative sun damage (low‐CSD) melanoma, both of which had a BRAF V600E mutation. A 49‐year‐old man had a 45 × 43 × 15 mm semi‐pedunculated, pigmented tumor in his back but had no other systemic symptoms. Histopathology revealed a 2‐mm‐sized incidental focus of LCH within a large lesion of low‐CSD melanoma. Diffuse immunoexpression of CD1a, langerin/CD207, S100 protein, and BRAF (VE1) was observed in the focus of LCH. Sanger sequencing with microdissection confirmed BRAF V600E mutation in the component of LCH. Interestingly, the advanced melanoma also harbored the same BRAF V600E mutation, although the significance of this tumor combination is still unknown.